2022
DOI: 10.1021/acsaem.1c02824
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes of Spinel MCo2O4 (M = Mn, Fe, Co, Ni, and Zn) Electrocatalysts during the Oxygen Evolution Reaction Investigated by In Situ X-ray Absorption Spectroscopy

Abstract: A comparison of the electrochemical and physicochemical behavior of cobalt-based oxides with spinel structure MCo 2 O 4 (M = Mn, Fe, Co, Ni, and Zn) was conducted to investigate the effect of the oxidation state and cation distribution in the spinel on the electrocatalytic activity of the oxygen evolution reaction (OER) in an alkaline solution. Various spinel MCo 2 O 4 electrocatalysts were synthesized by a facile microwave-assisted synthesis and low-temperature annealing. The overpotential of these MCo 2 O 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 70 publications
1
61
1
Order By: Relevance
“…The Co K-edge X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) measurements were conducted on the beamline 9C at the Photon Factory (PF) synchrotron radiation facility (KEK, Japan) . For the XANES/EXAFS measurements, the sample powder was diluted by mixing with BN to obtain a pressed disk pellet with the diameter of 10 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The Co K-edge X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) measurements were conducted on the beamline 9C at the Photon Factory (PF) synchrotron radiation facility (KEK, Japan) . For the XANES/EXAFS measurements, the sample powder was diluted by mixing with BN to obtain a pressed disk pellet with the diameter of 10 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, other metal ions like Ni and Mn, when inserted into Co 3 O 4 to form NiCo 2 O 4 and MnCo 2 O 4 , respectively, can suppress the catalytic activity for the OER, 261 due to occupation of tetrahedral and octahedral sites in the Co 3 O 4 spinel structure. In addition, M. Harada, F. Kotegawa, & M. Kuwa 16 demonstrated that the active sites are controlled by the balance of M 3+ /M 2+ cation distribution in O h and T d sites and by the bond strength between M and oxygen atoms at the electrocatalyst surface before and after the exposure to OER conditions, where the catalytic activity of the OER decreases in the order of ZnCo 2 O 4 > NiCo 2 O 4 > FeCo 2 O 4 > Co 3 O 4 > MnCo 2 O 4 .…”
Section: Znco2o4-based Electrocatalysts For Energy Conversion and Sto...mentioning
confidence: 99%
“…Its multifunctionality and excellent electrochemical properties are closely related to its structure which presents a regular spinel structure where Zn 2+ only replaces Co 2+ in the T d sites in Co 3 O 4 , leaving the Co 3+ content in the O h sites unchanged, while Ni and Mn mainly occupy O h sites in NiCo 2 O 4 and MnCo 2 O 4 . 16 In fact, the effect of the oxidation state and cation distribution in the spinel on the electrocatalytic activity for the OER in an alkaline solution has been studied, and a comparison of the electrochemical and physicochemical behavior of MCo 2 O 4 (where M = Mn, Fe, Co, Ni, and Zn) was made by M. Harada, F. Kotegawa, & M. Kuwa. 16 Interestingly, their catalytic activity for the OER follows the order: ZnCo According to the authors, the active sites for the OER are M 3+ species in the octahedral site, and their activities are significantly dependent on the Co 3+ /Co 2+ and M 3+ /M 2+ content ratios in the octahedral site as demonstrated according to XPS and in situ X-ray absorption fine structure (XAFS) measurements, demonstrating the importance of the presence of Zn 2+ ions in ZnCo 2 O 4 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations